2010
DOI: 10.1111/j.1751-1097.2010.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impacts of Solar UV Radiation on Photosynthetic Carbon Fixation from the Coastal to Offshore Surface Waters in the South China Sea

Abstract: We carried out experiments during an expedition (14 August to 14 September, 2007) that covered up to 250,000 km(2) to investigate the effects of solar UV radiation (UVR, 280-400 nm) on the photosynthetic carbon fixation of tropical phytoplankton assemblages in surface seawater of the South China Sea. From coastal to pelagic surface seawaters, UV-B (280-315 nm) caused similar inhibition, while UV-A (315-400 nm) induced photosynthetic inhibition increased from coastal to offshore waters. UV-B resulted in an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 44 publications
1
49
0
1
Order By: Relevance
“…Solar irradiation was known to be lower at the DCM with much more short-waveband blue light [35]; only larger phytoplankton cells can utilize short-waveband energy for photosynthesis [4,36]. Growth of smaller cells at this layer might thus be inferior to their larger counterparts, leading to a negative correlation of pico-cells in proportion to the DCM depth (r = −0.53, P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solar irradiation was known to be lower at the DCM with much more short-waveband blue light [35]; only larger phytoplankton cells can utilize short-waveband energy for photosynthesis [4,36]. Growth of smaller cells at this layer might thus be inferior to their larger counterparts, leading to a negative correlation of pico-cells in proportion to the DCM depth (r = −0.53, P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…In surface oceans, a series of environmental factors are known to control the biomass and distribution of phytoplankton. Light intensity influences phytoplankton growth and productivity through driving or photoinhibiting photosynthesis [3,4], while vertical mixing affects carbon fixation ability by balancing the damage and repair at high or low light levels [5,6]. The available trace metals (e.g., copper and iron) also lead to variations in phytoplankton biomass or size communities [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, some differences might arise when considering the responses on more dense cultures (Guan and Gao, 2010) with shorter wavelengths of UVB causing more damage to photosynthesis than to calcification, and longer wavelengths of UVA resulting in a decrease of calcification; in general terms, large cell density affects the control of the carbonate system (Gattuso et al, 2010). The irradiance levels of PAR, UVA and UVB used by us in our experiments were respectively about 18.1, 43.6 and Sea where coccolithophores are abundant (Ho et al, 2010;Li et al, 2011). Previous studies (Guan and Gao, 2010) indicated that E. huxleyi response changed with the irradiance and this was the base to use BWFs with an exposure response model based on irradiance (Neale and Kieber, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Very interesting consequences follow from the fact that different species of PP have differential sensitivity, that is, different ability to stand against UV-induced damages [11]. That means that during the periods of enhanced UV radiation some changes in structure of plank- ton communities take place.…”
Section: Climate Change Sun and Life In The Oceanmentioning
confidence: 99%
“…Second, with similar PP concentration, the effects will be maximum in zone with maximum solar illumination, that is, in tropics. Third, effects of UV irradiation can considerably differ in coastal and open ocean due to difference in prevailing PP species (Li et al, 2011). The most important consequences of PP concentration and corresponding light penetration fluctuations for ocean and atmosphere circulation are analyzed by Gnanadesikan and Anderson [10] using a coupled climate model.…”
Section: Climate Change Sun and Life In The Oceanmentioning
confidence: 99%